2019
DOI: 10.1186/s12935-019-0900-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation-based classification and identification of renal cell carcinoma prognosis-subgroups

Abstract: Background Renal cell carcinoma (RCC) is the most common kidney cancer and includes several molecular and histological subtypes with different clinical characteristics. The combination of DNA methylation and gene expression data can improve the classification of tumor heterogeneity, by incorporating differences at the epigenetic level and clinical features. Methods In this study, we identified the prognostic methylation and constructed specific prognosis-subgroups based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Still, such analyses may well overlook more subtle or focal changes of the methylome and at least for adult glioblastoma some degree of temporal evolution has been reported . Nonetheless there seems to be a relative persistence of the tumoral methylation pattern which provides the foundation for the utility of DNA methylation‐based analyses for cell lineage tracing and by extension, the identification of the origin of metastases of unknown primaries and the rapidly developing field of DNA methylation‐based tumour classification . A graphical summary of the evolution of the field within the context of brain tumours is displayed in Figure .…”
Section: Dna Methylation In Cancermentioning
confidence: 99%
“…Still, such analyses may well overlook more subtle or focal changes of the methylome and at least for adult glioblastoma some degree of temporal evolution has been reported . Nonetheless there seems to be a relative persistence of the tumoral methylation pattern which provides the foundation for the utility of DNA methylation‐based analyses for cell lineage tracing and by extension, the identification of the origin of metastases of unknown primaries and the rapidly developing field of DNA methylation‐based tumour classification . A graphical summary of the evolution of the field within the context of brain tumours is displayed in Figure .…”
Section: Dna Methylation In Cancermentioning
confidence: 99%
“…For example, genotyping methods based on genomics have been widely used to classify tumors, thus conducting the clinical trials. Recent studies have confirmed that DNA methylation provide insights into various tumor early diagnosis, molecular classification, and precise treatment [34,14,30].…”
Section: Discussionmentioning
confidence: 96%
“…DNA methylation is a posttranslational modification process, which are selectively occurred on the cytosines of 5′-CpG-3′ to generates 5-methyldeoxycytidine. The aberrant of DNA methylation, especially in CpG-rich regions (CpG islands), has been found closely related with physio-pathologic mechanisms underlying an array of human diseases [14]. Moreover, CpG islands was frequently detected in the promoter regions of the structural transcription gene [15], and abnormal CpG island hypermethylation of various tumor suppressor genes and hypomethylation of oncogenes play vital role in carcinogenesis [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed molecular mechanisms that underlie RCC development remain poorly understood. However, an increasing number of studies have determined that the inactivation of TSG is frequently involved in the tumorigenesis of RCC as a result of epigenetic abnormalities in DNA methylation [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%